1999
DOI: 10.1523/jneurosci.19-08-03050.1999
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin and English Single Word Processing Studied with Functional Magnetic Resonance Imaging

Abstract: The cortical organization of language in bilinguals remains disputed. We studied 24 right-handed fluent bilinguals: 15 exposed to both Mandarin and English before the age of 6 years; and nine exposed to Mandarin in early childhood but English only after the age of 12 years. Blood oxygen level-dependent contrast functional magnetic resonance imaging was performed while subjects performed cued word generation in each language. Fixation was the control task. In both languages, activations were present in the pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
192
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(214 citation statements)
references
References 31 publications
18
192
2
2
Order By: Relevance
“…Previous studies showed that these regions would be activated in bilingual production tasks and other bilingual processing tasks involving phonological and semantic retrieval (Bleser et al, 2003;Chee et al, 1999Chee et al, , 2001Chee et al, , 2003Klein et al, 1995Klein et al, , 1999Klein et al, , 2006Price et al, 1999;Tan et al, 2005).…”
Section: Imaging Resultsmentioning
confidence: 99%
“…Previous studies showed that these regions would be activated in bilingual production tasks and other bilingual processing tasks involving phonological and semantic retrieval (Bleser et al, 2003;Chee et al, 1999Chee et al, , 2001Chee et al, , 2003Klein et al, 1995Klein et al, , 1999Klein et al, , 2006Price et al, 1999;Tan et al, 2005).…”
Section: Imaging Resultsmentioning
confidence: 99%
“…This interpretation must be reconciled with the limited findings derived from other imaging investigations of language production in early bilinguals (Chee et al, 1999a;Kim et al, 1997). Kim et al (1997) studied early and late bilinguals.…”
Section: Discussionmentioning
confidence: 96%
“…Only a few functional neuroimaging studies in bilinguals have specifically addressed these interesting issues (Chee et al, 1999a(Chee et al, ,b, 2001Dehaene et al, 1997;Illes et al, 1999;Kim et al, 1997;Klein et al, 1994Klein et al, , 1995Perani et al, 1996Perani et al, , 1998Price et al, 1999). The results of these neuroimaging studies were recently summarized (Abutalebi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two brain regions are critical for language processing (e.g., Chee et al, 1999;Petersen et al, 1990;Poldrack et al, 1999;Price et al, 1996;Tan et al, 2000). In terms of the role of the language areas in the processing of mathematical terms, two other issues need to be discussed.…”
Section: The Language Areas and The Processing Of Mathematical Termsmentioning
confidence: 99%